THE BIG FIVE PERSONALITY, PEMETAAN KEPRIBADIAN PENGUSAHA UMKM UNTUK MENINGKATKAN INOVASI UMKM DI KOTA PANGKALPINANG - Hamsani, Hamsani; Yanuar, Dony; Wibawa, Dian Prihardini (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2020)
MSMEs in Bangka Belitung Islands Province experienced several obstacles in developing their MSMEs. Data for 2018 shows that the number of MSMEs in Bangka Belitung Kepulauang Province has decreased dramatically. The decreasing number of MSMEs from active to inactive, because these MSMEs are less able to survive in the increasingly fierce competition, so only MSMEs that survive are MSMEs that have creations and innovations according to needs of community Weak dimensions in the big five personality reflecting the unpreparedness of SMEs to compete and synergize. This study wants to see how the objective conditions dimensions big five personality SMEs in City of Pangkalpinang. The sample of study was Pangkal Pinang City SMEs practitioners with quantitative research methods processed from results of questionnaires. results of study showed that Openness to experience, Conscientiousness, Extroversion, and Agreeablenss, had a positive and significant effect on increasing MSMEs in Pangkalpinang City, while Neuroticm had a negative and significant effect on increasing MSMEs in Pangkalpinang City.